2015
DOI: 10.1016/j.cell.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Myocardin-Related Transcription Factor A Regulates Conversion of Progenitors to Beige Adipocytes

Abstract: SUMMARY Adipose tissue is an essential regulator of metabolic homeostasis. In contrast with white adipose tissue, which stores excess energy in the form of triglycerides, brown adipose tissue is thermogenic, dissipating energy as heat via the unique expression of the mitochondrial uncoupling protein UCP1. A subset of UCP1+ adipocytes develop within white adipose tissue in response to physiological stimuli, however, the developmental origin of these “brite” or “beige” adipocytes is unclear. Here, we report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
146
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 88 publications
15
146
0
Order By: Relevance
“…By RT-qPCR analysis, the MRTF-A transcript was reduced by 80%. The presence of MRTF-A transcript in dKO muscle is expected based on the MRTF-A targeting strategy and is consistent with previously published reports (Costello et al, 2015;Li et al, 2006;McDonald et al, 2015). The original targeting strategy for generating the MRTF-A null mice led to the splicing of exon 8 to exon 12 and production of a transcript with an in-frame fusion.…”
Section: Mrtf Dko Mice Fail To Thrive and Have Defects In Muscle Devesupporting
confidence: 88%
See 1 more Smart Citation
“…By RT-qPCR analysis, the MRTF-A transcript was reduced by 80%. The presence of MRTF-A transcript in dKO muscle is expected based on the MRTF-A targeting strategy and is consistent with previously published reports (Costello et al, 2015;Li et al, 2006;McDonald et al, 2015). The original targeting strategy for generating the MRTF-A null mice led to the splicing of exon 8 to exon 12 and production of a transcript with an in-frame fusion.…”
Section: Mrtf Dko Mice Fail To Thrive and Have Defects In Muscle Devesupporting
confidence: 88%
“…The MRTF/SRF axis is not only crucial for skeletal muscle and cardiac development, but also important for several other biological processes, such as the development of the hematopoietic system (Costello et al, 2015), thymocyte development (Costello et al, 2010;Mylona et al, 2011), glucose and lipid metabolism (McDonald et al, 2015;Sward et al, 2016), and neuronal development and motility (Kalita et al, 2012;Knoll, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…on April 27, 2019 http://stke.sciencemag.org/ Downloaded from adipogenesis (27,28,48,49). However, restriction of Jak inhibition to the commitment phase only affected cPGI 2 -stimulated beige adipocyte differentiation (Figs.…”
Section: (E)mentioning
confidence: 91%
“…8 Over the past several years, the field of brown and beige fat biology has seen an increase in the number of reports implicating various growth factors and cytoskeleton dynamics in the regulation of brown and beige fat development. More recently, we and others have demonstrated that beige adipocytes arise from a smooth-muscle origin, 10,12 suggesting that morphogenetic signals may regulate a cell fate switch between smooth muscle cells and beige adipocytes. In this review, we will focus on the effects of morphogens on cell shape and cytoskeleton dynamics.…”
Section: Introductionmentioning
confidence: 87%
“…We have demonstrated that overexpression of MRTFA in MCSs inhibits adipogenesis and MRTFA null mice are protected from diet-induced obesity and exhibit UCP1C multilocular cells, establishing MRTFA as a regulator of beige adipocyte development. 12 Stromal vascular cells from MTRFA null mice exhibit enhanced beige adipogenesis and reduced expression of smooth muscle proteins, suggesting that MRTFA regulates the switch between smooth-muscle cells and beige adipocytes in progenitors. Our recent data indicate that MRTFA also regulates the balance between adipogenesis and osteogenesis in bone-marrow derived MSCs, and MRTFA null mice exhibit decreased bone mass and increased marrow fat.…”
Section: Myocardian-related Transcription Factor Amentioning
confidence: 99%